If a 1 , a 2 , a 3 , … are in arithmetic progression , what is the expression equal to?
a 1 + a 2 1 + a 1 + a 2 1 + … + a n + a n + 1 1
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Since a 1 , a 2 , a 3 , ⋯ a n + 1 are in arithmetic progression so their general term can be represented as:
a k = a 1 + ( k − 1 ) d where d is the common difference between two consecutive terms of progression.
We have
a 2 − a 1 = d , a 3 − a 2 = d , a 4 − a 3 = d and in general
a k + 1 − a k = d ∀ k = 1 to n
Now coming to our expression,
a 1 + a 2 1 + a 2 + a 3 1 + ⋯ + a n + a n + 1 1
There are total n terms. Multiplying a k + 1 − a k in both numerator and denominator of k th term ( k = 1 to n ) of the above expression we get
( a 1 + a 2 ) ( a 2 − a 1 ) a 2 − a 1 + ( a 2 + a 3 ) ( a 3 − a 2 ) a 3 − a 2 + ⋯ + ( a n + a n + 1 ) ( a n + 1 − a n ) a n + 1 − a n
= a 2 − a 1 a 2 − a 1 + a 3 − a 2 a 3 − a 2 + ⋯ + a n + 1 − a n a n + 1 − a n
= d a 2 − a 1 + d a 3 − a 2 + ⋯ + d a n + 1 − a n
= d a 2 − a 1 + a 3 − a 2 + ⋯ + a n + 1 − a n
= d a n + 1 − a 1
Multiplying a n + 1 + a 1 in both numerator and denominator we get
d ( a n + 1 + a 1 ) ( a n + 1 − a 1 ) ( a n + 1 + a 1 )
= d ( a n + 1 + a 1 ) a n + 1 − a 1
= d ( a n + 1 + a 1 ) a 1 + n d − a 1
= d ( a n + 1 + a 1 ) n d
= a n + 1 + a 1 n